Laparoscopic Assisted Vaginal Hysterectomy, Setting Up a Service at a Peripheral Teaching Hospital. Issue 2 (1996) - Tsaltas, Jim; Kovacs, Gab; Dennis, Jenny; Pratt, Amanda
Abstract : The establishment of a laparoscopically assisted hysterectomy program at Box Hill Hospital is described. The first eight cases have been reviewed and recommendations are made to other gynaecology units who wish to establish a minimally invasive gynaecological surgery unit.